Modern video recording systems of motor techniques: practical aspect - Vako, Ilia (Pedagogy and Psychology of Sport, 2019)
Topicality. The end of the XX and beginning of the XXI century has been marked by the introduction of information technology to didactic biomechanics. Software and hardware systems that allow real-time processing of data uploaded to the computer have become widespread. The task of the study is to analyse the technique of "elbow lever outward" drill, performed by cadets of the fourth year of study using the optoelectronic system "Qualisys". Research methods. To achieve the set tasks, we have applied such research methods as analysis of scientific and methodological literature as well as documentary materials, methods of registration and analysis of athlete’s movements (system of video recording and analysis of athlete’s movements, 3D recording of human movements "Qualisys Motion Capture"). The results obtained during the study have been processed with the help of mathematical statistics methods. Results of the research. The duration of actions when performing "elbow lever outward" drill by cadets with the first blow of the hand is an average of 3,150 s (S = 0,101). The first movement involves performing swing or propulsion with the right hand. This action, according to experimental data, involves the pelvis and torso (a counter-clockwise movement). In 0.406 s (S = 0.050) after the start of the action, the cadet strikes with the right hand on the imaginary offender’s torso (usually in the chest area). Capture of imaginary offender’s right hand by the cadet with their left hand occurs in 0,298 s (S = 0,048) after blow. In another 0.237 s (S = 0.034) the cadet of the fourth year of study additionally fixes the imaginary offender’s hand, performing its capture with their right hand. Thus, for complete fixation of the detainee’s right hand (for the purpose of further performance of the drill) cadets spend more than 0,500 s. Further actions are related to the removal of the detainee’s body from equilibrium, which is achieved by lateral twisting of their right hand and forearm, causing pain for imaginary offender and making them manageable, thus, allowing the cadet by further withdrawal of the imaginary offender’s hand back (relative to the latter) lower the offender to the floor and make further rotational movement of their body already on the support area. Conclusions. At present, one of the most important aspects of didactic biomechanics is the arrangement of learning process for studying laws and patterns of motor actions. A key element of the learning process regarding the patterns of motor actions, in our opinion, is the use of video recording systems and application packages for biomechanical analysis. Currently, in the sports practice, the analysis of sports technique is inconceivable without the use of high-precision measuring equipment, which allows the specialist to assess both the inner and outer sides of the movement. In experimental studies conducted in the laboratory, we have simulated the situation of the employee’s capture of an imaginary offender during their walk with the help of performing "elbow lever outward" drill technique on detainee’s both right and left sides. The analysis of the obtained data shows the absence of statistically significant differences between the indicators of "elbow lever outward" drill, which was carried out both on the right and on the left sides of the detainee in the laboratory conditions (p> 0.05). The data of the pedagogical experiment allowed determining the quantitative indicators of "elbow lever outward" drill performed by cadets during 4 years of their study.